Salmonella enterica isolates from Western Australian rangeland goats remain susceptible to critically important antimicrobials. Issue 1 (December 2018) - Al-Habsi, Khalid; Jordan, David; Harb, Ali; Laird, Tanya; Yang, Rongchang; O'Dea, Mark; Jacobson, Caroline; Miller, David; Ryan, Una; Abraham, Sam
Abstract This study investigated faecal carriage and antimicrobial resistance (AMR) ofSalmonella enterica recovered from rangeland goats. Faecal samples (n = 400) were collected at slaughter from four consignments of goats (n = 100 samples per consignment), each from one of four localities in Western Australia. Carriage ofSalmonella spp. was detected in 106 samples (26.5%; 95% CI 22.4–31.0%). The rate of faecal carriage for each consignment ranged between 23–30%. PCR assays targeting the STM2755 and STM4497 genes revealed 84.9% (90/106) of the isolates were of serovar Typhimurium.Salmonella Chester (11/106, 10.4%) andS . Saintpaul (5/106, 4.7%) were characterised at invA and ompF genes. Antimicrobial susceptibility testing demonstrated that 84.0% of isolates were susceptible to all tested (n = 13) antimicrobials. Resistance was identified to azithromycin (14.2%), tetracycline (10.4%), ampicillin (5.7%), amoxicillin–clavulanate and cefoxitin (3.8%), trimethoprim/sulfamethoxazole (1.9%), gentamicin and streptomycin (0.9%). No isolate was resistant to four or more antimicrobials, or to critically important antimicrobials such as fluoroquinolones and extended spectrum cephalosporins. This is the first study reporting AMR inSalmonella isolates from Australian rangeland goats. The rate of detection of AMR was very low, some resistance to low-importance drugs was present in theSalmonella population, despite the absence of active selection pressure.